Technological dental sealants: in vitro evaluation of material properties and antibiofilm potential - Witalo Pereira de Jesus; Luiza de Almeida Queiroz Ferreira; Washington Henrique Themoteo da Silva; Fernanda Vieira Belém; Ana Paula Turrioni; Cláudia Silami de Magalhães; Mila Fernandes Moreira Madeira; Ivana Márcia Alves Diniz; Marco Aurelio Benini Paschoal (BMC Oral Health)
Abstract Background Due to the launch of new self-etching and self-adhesive sealing materials combined with the release of bioactive ions in the dental market, this in vitro study aimed to compare physical values of surface roughness (RS), vickers microhardness (VM), compositional energy dispersive spectroscopy (EDS), scanning electron microscopy (SEM), microbiological tests (inhibition halo-HI and surface microbial adhesion-MAS) and mechanical microshear bond strength (MBS). Methods The following groups were analyzed: Beautisealant® self-etching sealant (Shofu)(G1), FluroShield® conventional sealant (Dentsply)(G2- Control Group), Flow Constic® self-adhesive/self-etching resin (DMG)(G3) and Beautifil Flow Plus F03® conventional resin (Shofu)(G4). For the physical and compositional tests, specimens were molded and submitted to finishing/polishing in a metallographic polisher. RS and VM were measured through 5 readings. For the HI test, specimens were exposed to S. mutans for 24 h in brain–heart infusion (BHI) agar under microaerophilic conditions, with the diameter of the HI (mm) measured by digital caliper. For the MAS test, a bacterial biofilm of S. mutans was induced for five days in BHI broth + 5% sucrose and measurement of CFU/ml (log 10 from serial dilutions). For the MBS test, specimens were made in bovine enamel with the addition of the experimental group FluroShield® (Dentsply) + Single Bond Universal® adhesive (3 M)(G5) and measured in a universal testing machine. Data were submitted to ANOVA and Tukey's post hoc tests (p < 0.05) using the SPSS software. Results Different compositions proven in the EDS test were not determinants of the promotion of different RS: G1 = 0,19 (± 0,07), G2 = 0,15 (± 0,053), G3 = 0,13 (± 0,046), G4 = 0,14 (± 0,056); HI: G1 = 17,7 (± 1,36), G2 = 18,7 (± 3,47), G3 = 18,9 (± 4,87), G4 = 17,9 (± 3,61) and MAS: G1 = 5,22 (± 0,12), G2 = 5,15 (± 0,15), G3 = 5,12 (± 0,20), G4 = 5,06 (± 0,24). However, statistically influenced the values of VM: G1 = 16,71 (± 1,93), G2 = 16,28 (± 4,91), G3 = 26,11 (± 3,46), G4 = 37.9 (± 4.87), promoted lesser bacterial adhesion (G4 = 5.06 ± 0.24), and demonstrated fluoride ion only in the G4. Higher MBS was found in the conventional materials G5 = 8.38 (± 2.05) and G2 = 6.28 (± 1.35). Conclusions Bioactive materials and self-adhesive/self-etching for sealing pits and fissures did not demonstrate superior mechanical and antimicrobial properties performance compared to conventional techniques.